2014
DOI: 10.1021/nl404237j
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbranched β-Cyclodextrin Polymer as an Effective Multidimensional Binder for Silicon Anodes in Lithium Rechargeable Batteries

Abstract: Polymeric binders play an important role in electrochemical performance of high-capacity silicon (Si) anodes that usually suffer from severe capacity fading due to unparalleled volume change of Si during cycling. In an effort to find efficient polymeric binders that could mitigate such capacity fading, herein, we introduce polymerized β-cyclodextrin (β-CDp) binder for Si nanoparticle anodes. Unlike one-dimensional binders, hyperbranched network structure of β-CDp presents multidimensional hydrogen-bonding inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
236
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 290 publications
(239 citation statements)
references
References 40 publications
2
236
0
1
Order By: Relevance
“…7) provides a good platform to form intimate adhesion with Si surface and preserve the mechanical integrity of the Si electrode, resulting in a stable cycle life. 60 Compared to Alg as a linear polymeric binder, a higher amount of b-CDp remained on the Si surface after washing with water, reflecting the strong adhesion of b-CDp. 1801 peeling test also proved that hyperbranched b-CDp has strong adhesion due to its multidimensional contacts with Si particles.…”
Section: Hyperbranched Polymeric Bindersmentioning
confidence: 96%
“…7) provides a good platform to form intimate adhesion with Si surface and preserve the mechanical integrity of the Si electrode, resulting in a stable cycle life. 60 Compared to Alg as a linear polymeric binder, a higher amount of b-CDp remained on the Si surface after washing with water, reflecting the strong adhesion of b-CDp. 1801 peeling test also proved that hyperbranched b-CDp has strong adhesion due to its multidimensional contacts with Si particles.…”
Section: Hyperbranched Polymeric Bindersmentioning
confidence: 96%
“…When examined as a binder for Si anodes, the β-CDp was found to have a self-healing effect where even Si particles that lost contact with the anode could be recovered by the binder. These particles could then contribute to the capacity of the anode again [221].…”
Section: Si Nanopowder Anode Materialsmentioning
confidence: 99%
“…To improve the interactions between nano-Si particles and a binder, they proposed hyperbranched polymeric binders with an increased number of contacts between the nano-Si particles and the binders, as shown in Fig. 17(a) [40]. A β-CDp binder with a hyperbranched main backbone creates a fractal-like structure-based network in the Si anode; its various bulky side groups are physically entangled with each other via hydrogen bonding and van der Waals force, as displayed in Fig.…”
Section: Copolymersmentioning
confidence: 99%
“…17(b). It was reported that this polymeric network created by the β-CDp binder accommodates a large volume expansion of Si during Li insertion and assists in the recovery of the interactions with Si after it loses contact with the binder at certain points during the Li extraction processs [40]. In addition, a further improvement of the electrochemical performance of Si anodes could be realized with a hybrid of the hyperbranched β-CDp binder and a one-dimensional (D) alginate binder.…”
Section: Copolymersmentioning
confidence: 99%
See 1 more Smart Citation